Konsep Manusia dalam Novel Supernova Episode Ksatria, Putri, dan Bintang Jauh Karya Dee - Umi Nurjanah (Jurnal Filsafat "WISDOM", 2006)
In the sense of human relationship --with their self,  others, world and God-- human conception which contained in SupernovaKsatria, Puteri dan Bintang jatuh episode by Dee,  was human aparadox creature, love, work as self expression and religiouscomprehension. In the novel, Dee supplies much new views anddenying the old values. It manifest in a new world and ideal lifemodel. In reality, however, the ideal world supplied by authorusually difficult to realize and does not easy to recev by thereaders. For, there are some imaginations that usually contradictto the real world. To realize the author’s view is not an easy effort,the real world is very complex and many factors affecting andforming it.